Implementing the Kumon 4.0 Method as an Interactive Medium for Learning Mandarin Vocabulary in the Mandarin Language Education Study Program at UM - Deva Fitri Anggraini; Aiga Ventivani; Li Jiaman (Nexus Publishing, 2026)
This study aims to describe the form and type of interjection based on its function in a Mandarin comic entitled 非人哉 [Fēi rén zāi] by 一汪空气 [Yī Wāng Kōng Qì]. The analysis of this study uses the theory according to Liu Yuehua, Pan Wenyu, dan Gu Wei. The method used is a qualitative method using a library research approach. Data collection techniques are carried out through documentation and notes. Data analysis techniques are carried out in three stages (1) selection, (2) reduction, (3) interpretation. The main data source in this study is the comic 非人哉 [Fēi rén zāi] Karya 一汪空气 [Yī Wāng Kōng Qì]. The data analyzed were taken from chapters 1 to 50. The results found 15 forms of interjections in 8 types of interjections based on their function of use, namely expressions expressing feelings of satisfaction, pride, pleasure, or happiness, expressions expressing anger, sighs, and sadness, expressions expressing admiration and envy, expressions expressing surprise, expressions expressing disapproval, complaining, and reprimanding, expressions expressing expressions of understanding or comprehension, expressions expressing exclamations and answers, expressions expressing expressions of asking the same thing and unexpected things. This study is expected to contribute to strengthening Linguistic studies in Mandarin literature and help students understand the meaning and function of interjections more deeply.